Oxalic acid-assisted thermal treatment of iron film to fabricate magnetite and hematite microstructures: Synthesis, morphology and growth mechanism. Issue 181 (13th June 2017) - Cai, Lihong; Feng, Shunzhen; Xu, Qin
ABSTRACT: Microstructures of iron oxides were synthesized through oxalic acid-assisted thermal treatment of sputtered iron film at ambient conditions. Microstructures such as polyhedron, ball-flower, blades and nanowires have been obtained on the glass substrate at different annealing temperatures. The morphology of samples was studied by means of SEM. The possible growth mechanism of is also discussed. The polyhedron is believed to be formed in a process of nucleation–up growth–conglomeration-self assembled and blade-like nanostructure in a diffusion process.